Relevansi Novel Perawan Remaja dalam Cengkraman Militer dalam Pembelajaran di SMA: Sebuah Analisis Konstruksi Gender - Lubis, Anisah; Laia, Junileti; Parinduri, Alfina Syahrina; Sari, Sartika; Septriani, Hilda (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study aims to analyze the gender construction portrayed in the novel Virgin of Adolescents in the Grip of the Military by Pramoedya Ananta Toer and its relevance as a teaching material in high school education. Written in 1941, the novel depicts the lives of women during the Japanese occupation in Indonesia, focusing on the struggles of women who faced obstacles imposed by military power. Amidst hardship and social inequality, women of that era had a strong desire to pursue higher education, despite the repression from the Japanese occupiers. This research employs a qualitative descriptive approach, analyzing intrinsic elements of the novel such as characters and themes, and connecting them to the historical-social context of the time. The findings show that the novel portrays women's resistance through radical actions as a response to gender injustice. Furthermore, the study discusses the relevance of this novel as a potential teaching material in high schools, based on interviews with Indonesian language teachers at SMA Swasta Nurani Belawan. The use of this novel is expected to enhance students' understanding of gender issues and foster a more equitable perspective on women's roles in history.